(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This research aimed to explore how the use of artificial intelligence (AI) technologies contributes to enhancing the effectiveness of digital leadership within private (smart) schools in Riyadh. This is achieved by empowering decision-makers, increasing operational efficiency, and improving the quality of leadership practices within the smart school environment. The sample consisted of 40 participants (e.g., 40 participants), with a majority being female (75%) compared to males (25%). The data also revealed that most participants were over 40 years old (55%), and the majority held a bachelor’s degree (77.5%). Furthermore, the data indicated that 85% of participants had more than five years of professional experience, and the majority held leadership or supervisory positions (85%). This strengthens the reliability of their opinions in assessing the level of digital maturity and the smart environment within the school, as well as its ability to develop AI-supported teaching and management practices. The results showed that the adoption of AI at the operational and analytical levels was associated with a higher level of digital leadership, particularly in governance and change management. This confirms that AI is a key and direct enabler of digital leadership within the school. One of the most important recommendations is the need to deepen the use of educational artificial intelligence technologies and expand their use in administrative and educational processes in a more integrated manner, which contributes to enhancing the quality of decision-making and building more effective educational and strategic models.